Cophinforma tumefaciens causing Dieback disease in Litsea cubeba (Lour.) Per. in China - Li, Ke Yu (Plant disease, 2024)
Litsea cubeba (Lour.) Per., named as May Cang, is a rare deciduous evergreen tree and cultivated for its ethnopharmacological properties and medicinal uses. In 2020-2023, an outbreak of dieback disease was observed on the stems and branches of L. cubeba with above 80% disease incidence in a 150 hectare plantation in Yiyang, Hunan (N28°39'24"; E112°12'48"). In the early stages, water-soaked lesions appeared on the stems and branches. The infected sites turned elliptical in shape, dark brown, and swelled. The infected branches and stems died gradually. After scraping the bark from the diseased stems and branches under aseptic conditions, diseased tissues (5 mm2) from the diseased-healthy junction were cut off and placed on PDA containing penicillin (50 mg/L) at 25 ℃ to 28 ℃ in the dark for 3 to 4 days. Colonies from different tissues were subcultured by transferring the hyphal tip onto fresh PDA. Colonies with regular margin on PDA reached 60 mm diam after 3 d at 25℃ to 28℃, the aerial mycelia were woolly, grayish-white at first, gradually turned gray black after 14 days. No fruiting bodies were found on medium. On disease stems, conidia were hyaline, aseptate, granular, ellipsoid to obovoid, 18.0 to 33.4 × 5.5 to 9.8 μm (av. 25.6 × 7.4 μm, n=55). The internal transcribed spacers (ITS), 28S nrDNA (LSU), elongation factor 1-alpha (TEF1), and β-tubulin (TUB2) of isolate ACCC35248 and ACCC35249 (stored in the Agricultural Culture Collection of China) were PCR amplified and sequenced for further identification with primer pairs: .ITS1/ITS4 (White et al. 1990), LROR/LR7 (Rehner et al. 1994), EF1-728F/EF-2 (Zhao et al. 2021) and TUB4Rd/TUB2Fd (Woudenberg et al. 2009), respectively. Obtained sequences of ITS, LSU, TEF1 and TUB2 (Genebank accessions nos. PP577627 and PP577624, PP588412 and PP588413, PP584319 and PP584320, PP584321 and PP584322) showed above 99% homology with these sequences of Cophinforma tumefaciens ex-type culture IMI 76762 (ITS: MW810287, TEF: MZ073950 and TUB: MZ073935) and MFLUCC 11-0425 (ITS: JX64680, LSU: JX646817, TEF: JX646865 and TUB: JX646848) (Liu et al, 2012). Phylogenetic analysis with maximum likelihood in MEGA 10.0 using the concatenated ITS-TEF-TUB sequences placed the isolates within the C. tumefaciens clade with 100% bootstrap support. Therefore, the fungus was identified as C. tumefaciens. One-year-old healthy L. cubeba seedlings were surface-sterilized with 75% ethanol, then wounded with sterile needles and a 6-mm-diameter fungal plug of 14-day-old cultures grown on PDA was put on the wound. Sterile PDA plugs were used as controls, and all inoculated sites were wrapped with plastic film. The tests were repeated twice. At 7 days post-inoculation, symptoms were observed at the inoculated sites and the upper branches of the inoculation site died back two months later, while no symptoms were observed on the control plants. C. tumefaciens was re-isolated from the inoculated stems. C. tumefaciens can infect various plants and cause disease worldwide (Zhao et al. 2021), and this is the first report of a quarantine pathogen causing dieback on L. cubeba in China. This information will assist in preventing further spread of this pathogen